PERAN GOOD CORPORATE GOVERNANCE ATAS DETERMINAN KUALITAS LABA INDUSTRI DASAR DAN KIMIA DI INDONESIA - Wanlyeamin Arnold, Luturmas; Nurmala Ahmar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
This study aims to examine the effect of capital structure, profitability and liquidity onearnings quality with good corporate governance as moderation in basic industrialand chemical manufacturing companies on the Indonesia Stock Exchange from 2016 to2019. This research method uses quantitative research with SEM-based data analysis.variant using the WarpPls 7.0 application. The results of the analysis show that capitalstructure affects earnings quality, good corporate governance moderates the quasicapital structure on earnings quality, profitability does not affect earnings quality,good corporate governance does not moderate profitability on earnings quality.Liquidity does not affect earnings quality, good corporate governance does notmoderate liquidity on earnings quality